The economic impact of predation in the wildlife ranching industry in Limpopo, South Africa - Schepers, Anche (University of the Free State, 2016)
South Africa has always been rich in wildlife species, but the population size has varied greatly over the past century. The incentive provided by the Game Theft Act, Act 105 of 1991 as amended, allowed individuals to engage in natural resource based private enterprises and gave rise to the rapid development of the wildlife industry. Losses due to predation is a large problem, not only in the small and large livestock industries, but losses have also been incurred in the wildlife ranching industry. There is not much known regarding wildlife numbers in South Africa, due to the difficulty in counting wildlife. Even though there are uncertainties regarding wildlife numbers, the number of animals sold on game auctions increased by 16.7% per year since 2009. The wildlife industry grew rapidly the past decade and is currently the sixth largest agricultural commodity in South Africa; every year more agricultural land previously devoted to livestock or crops are devoted to wildlife ranching. This detailed study was conducted in all the provinces of South Africa. The dissertation focussed on the situation in the Limpopo province; basic information regarding the other Provinces of South Africa are included in Appendices. The primary objective of the dissertation was to determine the economic implication of predation on the wildlife ranching industry of the Limpopo province, South Africa. This was not an easy task because of the large variety of wildlife species and because it is difficult to count wildlife. The wildlife species (antelope) were divided into three groups based on the reported predation incurred on wildlife ranches, namely: large antelope species, small antelope species and scarce species/colour variant antelope. The direct cost is associated with the number of animals lost due to predation, this ZAR value was calculated per hectare for each of the species defined in the three groups. The indirect cost is the total cost associated with the prevention and control of predation. The total indirect cost was calculated as ZAR 26.15/ha. The results obtained by calculating losses for the defined three scenarios provided an indication of how large the predation losses are on wildlife ranches. Calculating the total cost for the entire wildlife sector may lead to over or underestimations; therefore the total cost were calculated/ha. Any wildlife rancher can use the baseline information and calculate his/her own financial losses; for example: a wildlife rancher who keeps nyalas on 5 000 ha can calculate his/her estimated total cost to be ZAR 593 765/year. A wildlife rancher who keeps blesbok on 12 000 ha can incur a total cost of ZAR 668 103/year and a wildlife rancher who keeps black impala and Livingston eland on 6 000 ha can calculate his/her total cost to be ZAR 11 957 637/year. It was concluded from these three scenarios that the losses due to predation, as caculated in all three groups, were large; this is in line with the hypothesis. Factors that influence the occurrence and the level of predation were also determined by using Probit and Truncated regression models, respectively. The variables affecting the occurrence and the variables affecting the level of predation were different, and the variables affecting the three different groups varied as well. Propensity Score Matching was used to determine whether the method of counting wildlife has an effect on the level of predation. The method of counting had an effect on the level of predation on large antelope species and scarce species/colour variants, but not on small antelope species. This dissertation provides information for wildlife ranchers to calculate the total cost due to predation on their own specific wildlife ranches. They can improve their management practices and choose appropriate control methods, whether non-lethal, methods assisting wildlife ranchers or lethal methods. They can also view and adopt the more appropriate method to count their wildlife species.
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 2016
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 2016
Keywords: Predation; Wildlife ranching; Large antelope species; Small antelope species; Scarce species; Colour variant antelope; Direct cost of predation; Indirect cost of predation; Propensity score matching; Wildlife management; Game farms--South Africa--Limpopo; Wildlife--Predators of